Tree monocultures in biodiversity hotspots : impact of pine plantations on the mammal assemblages of the Atlantic Forest and the Southern Cone Mesopotamian Savanna ecoregions of South America - Iezzi, María Eugenia (2016)
Fil: Iezzi, María Eugenia. Universidad Nacional de Misiones. Facultad de Ciencias Forestales; Argentina.